Chitosan / hyaluronic acid hydrogel based on nitrate ion regulation and control as well as preparation method and application of chitosan / hyaluronic acid hydrogel

Through the preparation method of nitrate ion-regulating chitosan/hyaluronic acid hydrogel, the problem of insufficient mechanical properties of hydrogels is solved, better mechanical properties and swelling properties are achieved, and it is improved in the fields of drug loading and dressing value of application.

CN119306986APending Publication Date: 2025-01-14ANHUI POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371827.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The mechanical properties of chitosan/hyaluronic acid hydrogels are poor and cannot meet the actual application needs.

Method used

Through nitrate ion regulation, the structure and performance of the hydrogel is adjusted using anionic effect, including heating and stirring sodium hyaluronate and chitosan in water, adding glacial acetic acid solution to form a hydrogel film, and containing nitrate ions After soaking in the solution, the deionized water is repeatedly cleaned and dried to regulate the mechanical properties and structure of the hydrogel.

Benefits of technology

The mechanical properties, swelling properties and drug-loading and release properties of the hydrogel have been significantly improved, and its application potential in the fields of drug loading and dressings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306986A_ABST
    Figure CN119306986A_ABST
Patent Text Reader

Abstract

The invention discloses chitosan / hyaluronic acid hydrogel based on nitrate ion regulation and control and a preparation method and application thereof, the preparation method comprises the following steps: (1) heating and stirring sodium hyaluronate in water until the sodium hyaluronate is completely dissolved, then adding chitosan, and stirring to uniformly disperse the chitosan; (2) slowly dropwise adding a glacial acetic acid solution into the solution obtained in the step (1) to completely dissolve the chitosan, and continuously stirring to react for 20-50 minutes; (3) standing and drying the reaction liquid obtained in the step (2) to form a hydrogel film; (4) soaking the dried hydrogel film in a solution containing nitrate ions, then repeatedly cleaning with deionized water until the pH value of water is neutral, and then drying; based on the anion effect, the structure and performance of the hydrogel are adjusted through nitrate ions, and the hydrogel composite membrane soaked with nitrate has excellent mechanical performance, swelling performance and good drug loading and releasing performance and can be used in the fields of drug loading and dressing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogel preparation, and particularly relates to a chitosan / hyaluronic acid hydrogel regulated by nitrate ions, and a preparation method and application thereof. Background Art

[0002] Hydrogel is a polymer material with a three-dimensional porous network structure formed by covalent or non-covalent crosslinking of macromolecules (chitosan, cellulose, alginate and polyvinyl alcohol, etc.) in a micro-aqueous environment. It can store a large amount of water and maintain its own network structure without being dissolved. It has the advantages of excellent cell compatibility, biodegradability and operability, and is widely used in biomedicine, agriculture, horticulture, soft electronics, 3D printing and environmental engineering.

[0003] However, the poor mechanical properties of hydrogels have hindered their practical application. Franz Hofmeister established the Hofmost series, which is of great scientific significance, that is, different types of salt solutions have different precipitation abilities for proteins or other colloids, and found that the effect of anions in salt solutions is significantly stronger than that of cations. The Hofmost effect is widely used in protein crystallization, protein folding, enzyme activity, colloid assembly and polymers, and is called a pearl in the history of physical chemistry by scientists.

[0004] Chitosan is the only alkaline polysaccharide obtained by deacetylation of the natural product chitin. It has positively charged amino groups and can adsorb negatively charged bacteria, thereby inhibiting or killing bacteria. Hyaluronic acid, also known as hyaluronic acid, is an acidic mucopolysaccharide that has the functions of lubricating joints and regulating the permeability of blood vessel walls. The carboxyl group of hyaluronic acid can react with the amino group of chitosan to form a hydrogel.

[0005] Although chitosan / hyaluronic acid hydrogel has good biocompatibility, the mechanical properties of the hydrogel prepared by the casting method are poor and cannot meet further practical applications. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a chitosan / hyaluronic acid hydrogel regulated by nitrate ions, and a preparation method and application thereof. Based on the anion effect, the structure and properties of the hydrogel are adjusted by nitrate ions. The hydrogel composite film after nitrate immersion has excellent mechanical properties, swelling properties, good drug loading and release properties, and can be used in the field of drug loading and dressing.

[0007] The technical solution adopted by the present invention is as follows:

[0008] A method for preparing chitosan / hyaluronic acid hydrogel based on nitrate ion regulation, the preparation method comprising the following steps:

[0009] (1) heating and stirring sodium hyaluronate in water until it is completely dissolved, and then adding chitosan and stirring to make it evenly dispersed;

[0010] (2) slowly adding glacial acetic acid solution to step (1) to completely dissolve the chitosan, and continuing to stir the reaction for 20 to 50 minutes;

[0011] (3) allowing the reaction solution obtained in step (2) to stand and dry to form a hydrogel film;

[0012] (4) The dried hydrogel membrane is immersed in a solution containing nitrate ions, and then repeatedly washed with deionized water until the pH of the water is neutral and then dried.

[0013] In step (1), the mass ratio of sodium hyaluronate to chitosan is 0.08-0.1:0.25-0.30.

[0014] In step (1), the concentration of sodium hyaluronate in water is 0.05-0.07 g / mL.

[0015] In step (1), the temperature of the heating and stirring is 40 to 60°C.

[0016] In step (2), the pH of the glacial acetic acid solution is 2-4.

[0017] In step (3), the drying temperature is 40-60°C.

[0018] In step (4), the solution containing nitrate ions is a copper nitrate solution.

[0019] In step (4), the concentration of the solution containing nitrate ions is 0.25-0.3 mol / L.

[0020] In step (4), the drying temperature is 40-60°C.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] (1) The present invention proposes for the first time that chitosan, hyaluronic acid and anion solution are the main components of a hydrogel. The hydrogel obtained under the dual effects of polyelectrolyte reaction and salting out has better mechanical properties and water absorption and retention properties than simple chitosan / hyaluronic acid hydrogel.

[0023] (2) The present invention proposes for the first time nitrate immersion treatment to regulate the structure and properties of chitosan / hyaluronic acid.

[0024] (3) After nitrate immersion, the structure of chitosan / hyaluronic acid hydrogel is more stable, and the mechanical properties of the hydrogel are improved under the condition of high swelling performance.

[0025] (4) After nitrate treatment, chitosan / hyaluronic acid hydrogel has ionic conductivity.

[0026] (5) The chitosan / hyaluronic acid hydrogel treated with nitrate ions and copper ions exhibits photothermal properties.

[0027] (6) After nitrate treatment, chitosan / hyaluronic acid hydrogel has a strong adsorption effect on negatively charged methyl orange.

[0028] (7) The chitosan / hyaluronic acid hydrogel prepared by the preparation method provided by the present invention can be used in the field of drug loading or dressing. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Mechanical properties of chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper nitrate in Example 1 (a), chitosan / hyaluronic acid hydrogel treated with 0.1 mol / L copper nitrate in Comparative Example 1 (e), chitosan / hyaluronic acid hydrogel treated with 0.5 mol / L copper nitrate in Comparative Example 2 (f), chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper sulfate in Comparative Example 3 (b), chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper chloride in Comparative Example 4 (c), and chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper acetate in Comparative Example 5 (d);

[0030] Figure 2 The chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper nitrate in Example 1 (a), the chitosan / hyaluronic acid hydrogel treated with 0.1 mol / L copper nitrate in Comparative Example 1 (e), the chitosan / hyaluronic acid hydrogel treated with 0.5 mol / L copper nitrate in Comparative Example 2 (f), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper sulfate in Comparative Example 3 (b), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper chloride in Comparative Example 4 (c), and the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper acetate in Comparative Example 5 (d) are swelling performance diagrams;

[0031] Figure 3The infrared spectra of the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper nitrate in Example 1 (a), the chitosan / hyaluronic acid hydrogel treated with 0.1 mol / L copper nitrate in Comparative Example 1 (e), the chitosan / hyaluronic acid hydrogel treated with 0.5 mol / L copper nitrate in Comparative Example 2 (f), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper sulfate in Comparative Example 3 (b), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper chloride in Comparative Example 4 (c), and the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper acetate in Comparative Example 5 (d);

[0032] Figure 4 The XRD spectra of the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper nitrate in Example 1 (a), the chitosan / hyaluronic acid hydrogel treated with 0.1 mol / L copper nitrate in Comparative Example 1 (e), the chitosan / hyaluronic acid hydrogel treated with 0.5 mol / L copper nitrate in Comparative Example 2 (f), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper sulfate in Comparative Example 3 (b), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper chloride in Comparative Example 4 (c), and the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper acetate in Comparative Example 5 (d);

[0033] Figure 5 Thermogravimetric and differential thermogravimetric graphs of the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper nitrate in Example 1 (a), the chitosan / hyaluronic acid hydrogel treated with 0.1 mol / L copper nitrate in Comparative Example 1 (e), the chitosan / hyaluronic acid hydrogel treated with 0.5 mol / L copper nitrate in Comparative Example 2 (f), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper sulfate in Comparative Example 3 (b), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper chloride in Comparative Example 4 (c), and the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper acetate in Comparative Example 5 (d);

[0034] Figure 6 Graphs showing the loading rates of methyl orange at different pH values ​​for chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper nitrate in Example 1 (a), chitosan / hyaluronic acid hydrogel treated with 0.1 mol / L copper nitrate in Comparative Example 1 (e), and chitosan / hyaluronic acid hydrogel treated with 0.5 mol / L copper nitrate in Comparative Example 2 (f);

[0035] Figure 7Graphs showing the release of methyl orange at different pH values ​​for chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper nitrate in Example 1 (a), chitosan / hyaluronic acid hydrogel treated with 0.1 mol / L copper nitrate in Comparative Example 1 (e), and chitosan / hyaluronic acid hydrogel treated with 0.5 mol / L copper nitrate in Comparative Example 2 (f);

[0036] Figure 8 The test results of the conductivity test results of the chitosan / hyaluronic acid hydrogel (a) treated with 0.3 mol / L copper nitrate in Example 1, the chitosan / hyaluronic acid hydrogel (b) treated with 0.3 mol / L copper sulfate in Comparative Example 3, the chitosan / hyaluronic acid hydrogel (c) treated with 0.3 mol / L copper chloride in Comparative Example 4, and the chitosan / hyaluronic acid hydrogel (d) treated with 0.3 mol / L copper acetate in Comparative Example 5;

[0037] Fig. 9 The test results of the photothermal response of the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper nitrate in Example 1 (a), the chitosan / hyaluronic acid hydrogel treated with 0.1 mol / L copper nitrate in Comparative Example 1 (e), the chitosan / hyaluronic acid hydrogel treated with 0.5 mol / L copper nitrate in Comparative Example 2 (f), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper sulfate in Comparative Example 3 (b), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper chloride in Comparative Example 4 (c), the chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper acetate in Comparative Example 5 (d), and the untreated chitosan / hyaluronic acid hydrogel in Comparative Example 6 (g);

[0038] Fig.10 These are the transparent zone test results of chitosan / hyaluronic acid hydrogel treated with 0.3 mol / L copper nitrate in Example 1 (a), chitosan / hyaluronic acid hydrogel treated with 0.1 mol / L copper nitrate in Comparative Example 1 (e), and chitosan / hyaluronic acid hydrogel treated with 0.5 mol / L copper nitrate in Comparative Example 2 (f) on Escherichia coli and Staphylococcus aureus. DETAILED DESCRIPTION

[0039] The present invention is described in detail below with reference to the embodiments.

[0040] Example 1

[0041] A method for preparing chitosan / hyaluronic acid hydrogel based on nitrate ion regulation comprises the following steps:

[0042] (1) Accurately weigh 100 mg of sodium hyaluronate and completely dissolve it in 15 mL of deionized water at 45°C and 500 rpm, then add 300 mg of chitosan and stir for 5 min to make it evenly dispersed;

[0043] (2) Slowly add 4 mL of pH 2.2 glacial acetic acid solution at a rate of one drop per minute and continue stirring at 45 °C and 500 rpm for 30 min;

[0044] (3) slowly pouring the above solution into a culture dish and drying it at 45°C to form a hydrogel;

[0045] (4) The dried hydrogel was immersed in 30 mL of 0.3 mol / L copper nitrate solution for 12 h, washed repeatedly with deionized water until the pH value remained unchanged, and dried in an oven at 45 °C.

[0046] Comparative Example 1

[0047] The rest is the same as in Example 1, except that in step (4), the dried hydrogel is immersed in 30 mL of 0.1 mol / L copper nitrate solution for 12 h.

[0048] Comparative Example 2

[0049] The rest is the same as in Example 1, except that in step (4), the dried hydrogel is placed in 30 mL of 0.5 mol / L copper nitrate solution and immersed for 12 h.

[0050] Comparative Example 3

[0051] The rest is the same as in Example 1, except that in step (4), the dried hydrogel is placed in 30 mL of 0.3 mol / L copper sulfate solution and immersed for 12 h.

[0052] Comparative Example 4

[0053] The rest is the same as in Example 1, except that in step (4), the dried hydrogel is placed in 30 mL of 0.3 mol / L copper chloride solution and immersed for 12 h.

[0054] Comparative Example 5

[0055] The rest is the same as in Example 1, except that in step (4), the dried hydrogel is placed in 30 mL of 0.3 mol / L copper acetate solution and immersed for 12 h.

[0056] Comparative Example 6

[0057] The rest is the same as in Example 1, except that step (4) is not performed.

[0058] Test Case

[0059] The structural breaking strength, breaking elongation, elastic modulus, swelling performance, etc. of the hydrogels obtained in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were tested and characterized, and the hydrogels in Example 1 and Comparative Examples 1 and 2 were subjected to drug model loading, release and antibacterial performance testing of negatively charged drug sodium lauroyl sarcosinate, and the results are shown below.

[0060] 1. Mechanical properties testing

[0061] The hydrogel films obtained in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were subjected to uniaxial tensile tests using a texture analyzer. The hydrogel film samples were cut into strips with a length of 50 mm, a width of 10 mm and a thickness of 0.2 mm. The measurement range was 5000 cN, the preload force was 10 cN, the clamp distance was 30 mm, and the tensile rate was 2 mm / s. The measurement results are shown in FIG. Figure 1 The Young's modulus of the chitosan / hyaluronic acid hydrogel treated with copper nitrate in Example 1 is significantly higher than that in Comparative Examples 3, 4 and 5. - and CH3COO in Comparative Example 5 - The chaotropic ability is strong. The two interfere with the hydration of macromolecules by increasing the surface tension of the cavity around the skeleton, destroying the connection between the hydrogel groups, destroying the original network structure, and causing the mechanical properties to decline. Since the structure of the hydrogel treated under pure water conditions (without Hofmeister effect) is completely destroyed, the hydrogel network collapses, and its mechanical properties cannot be measured. - and CH3COO - The chaotropic effect will destroy the network structure, but copper ions can participate in the complexation of polymer chains and enhance the stability of its network. The effects of these two interact synergistically, allowing the hydrogel to still maintain the integrity of its network structure. It has strong lyophilicity and can interact with water molecules on the surface of macromolecules, thereby destroying the hydration layer on the surface of the group, allowing the groups in the network that cannot combine due to the hydration layer to interact with each other, thereby strengthening its network structure. Effects on hydrogels CI - and CH3COO - Completely different. Although it belongs to the category of chaotropic salts, according to the Hofmost sequence, the order of the forces of acid radical ions is And the chaotropic ability is stronger than CI - , but its mechanical properties are stronger than CI - and CH3COO - , and the swelling performance is higher than This may be because Not only do they act as lyophilic and chaotropic agents, but they also act as small molecule cross-linkers that interact with polymer chains, thus giving them high mechanical properties.

[0062] 2. Swelling properties

[0063] The films obtained in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were dried to completely remove moisture, and the dried samples were immersed in distilled water and weighed once after 5 minutes, and then weighed every 10 minutes until the re-weighing weight reached a constant (W w : Weight of hydrogel after stabilization; W d : sample dry weight).

[0064]

[0065] The results are as follows Figure 2 As shown, The hydrophilicity of Cl makes the groups of the hydrogel interact as much as possible, and the enhancement of the mechanical properties at the macro level also means the compactness of the hydrogel network structure at the micro level, so its swelling performance is poor. - and CH3COO - It is a chaotropic salt, and a large number of groups in its network still do not interact with each other. Moreover, the density of its network structure allows the hydrogel to accommodate a large amount of water, and the hydrophilic groups present can form hydrogen bonds with water molecules, thus making the swelling performance higher. When participating in the bonding reaction in the hydrogel as a small molecule, it not only retains some of the hydrophilic groups existing in the hydrogel, but also brings in some of the hydrophilic groups, making the swelling performance of the hydrogel better. The processing is higher. Figure 1 and Figure 2 It can be seen that the swelling performance of the chitosan / hyaluronic acid hydrogel (Example 1) treated with copper nitrate is about 23% lower than that of copper chloride (Comparative Example 4), but the toughness and Young's modulus of the hydrogel treated with copper nitrate are 68% and 61% higher than those of the hydrogel treated with copper chloride. The toughness of the hydrogel treated with copper sulfate (Comparative Example 3) is 23% higher than that of the hydrogel treated with copper nitrate, but the swelling performance is about 50% lower. Therefore, considering the comprehensive mechanical properties and swelling performance, Example 1 is significantly higher than Comparative Examples 3, 4 and 5.

[0066] 3. Infrared detection

[0067] The hydrogels obtained in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were tested by Fourier transform infrared spectrometer. Figure 3 As shown, at 630cm -1There is a broad peak everywhere, which is caused by the vibration of Cu-O bond. At 1117cm -1 A new peak was found, which is the characteristic peak of sulfate. It also participates in the interaction between hydrogel polymer chains, rather than just destroying the interaction between polymer chains and water. The strong lyophilic effect is greater than the interaction with the polymer chain, so only a weak peak appears in the infrared at 1379cm -1 Department, A new strong and sharp peak appeared in the treated hydrogel, belonging to characteristic peaks, which means that there are a lot of Combined with polymer chains, as small molecules, participate in the assembly of hydrogel internal chains. - and CH3COO - No new peaks appear, so these two anions do not participate in the cross-linking of the chains, but only play the role of chaotropic salts, that is, another role of ions, which increases the surface tension of the cavities around the skeleton to interfere with the hydrophobic hydration of macromolecules, thus leading to the collapse of the polymer network.

[0068] 4. XRD detection

[0069] The films obtained in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were dried to completely remove moisture, and then dried in an oven at 45°C for 24 hours. The films were cut into squares with a length and width of about 1.5 cm, and the X-ray diffraction spectra of the hydrogels were recorded using an X-ray diffractometer. The results are shown in FIG. Figure 4 As shown. CH3COO - With Cl - The treated chitosan / hyaluronic acid hydrogel still has the characteristic peak of chitosan at around 2θ=10°, which means that these two anions do not destroy the crystalline structure of chitosan, especially CH3COO - The chitosan peak of the treated hydrogel is more obvious. - and CH3COO - Compared with the treated hydrogels, and The crystallization peak of hydrogel chitosan treated with and The crystallization peak of chitosan hydrogel treated with MgCl2O3 was reduced.

[0070] 5. Thermogravimetric testing

[0071] The hydrogels of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were dried to completely remove moisture, and about 5 mg of the hydrogel was placed in a ceramic crucible, and the thermal stability of the hydrogel was measured at 30-700°C, a rising temperature of 10°C / min, a protective atmosphere of nitrogen, an experimental atmosphere of oxygen, and a rate of 20 mL / min. The results are shown in FIG. Figure 5 As shown, the hydrogels treated with four anions all have two-stage weight loss curves, which are consistent with the Cl - and CH3COO - Compared with the treated hydrogels, and The treated hydrogel has a lower crystallinity, so its thermal stability is also reduced. and The thermal weight loss temperature of the treated hydrogel is lower, especially the weight loss curve of the second stage. and The second stage weight loss temperature is lower than that of CH3COO - Treated at nearly 50℃, CI - The treatment temperature is nearly 100℃. According to the final copper ion content, although the concentration of 0.5mol / L copper nitrate is high, the Cu that can interact with the hydrogel is 2+ The content was the lowest, which may be due to the high concentration of The chaotropic effect is strong, so that the polymer chain can bind a large amount of water and cannot bind to Cu 2+ Complexation occurs, and the pH of high concentration copper nitrate is low. Low pH can directly reduce the structural density of the chitosan skeleton, resulting in the combined Cu 2+ Therefore, the Hofmost effect based on anions and its interaction with Cu 2+ The synergistic effect is the main reason for improving the mechanical properties of hydrogels.

[0072] 6. Methyl orange loading test

[0073] Methyl orange was used as a negatively charged model drug to evaluate the ability of chitosan / hyaluronic acid hydrogels treated with copper nitrate to load negatively charged drugs at different pH values. 50 mg of the dried hydrogels of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were placed in 4 mL of a 0.01 mg / mL methyl orange solution, and the absorbance of the solution was measured at 37°C and 150 rpm for different time periods. After reaching loading equilibrium, the final methyl orange loading rate of the hydrogel was calculated according to the following formula (A0: initial absorbance, A t : Loading absorbance at different times):

[0074]

[0075] The results are as follows Figure 6 As shown in the figure, with the increase of pH value, the loading rate of hydrogel for methyl orange shows a trend of first increasing and then decreasing. It is well known that the adsorption performance of hydrogel is related to its own pore size, functional groups and charge. The pH response performance is more closely related to the charge carried by the hydrogel itself. After swelling in a buffer solution with a high pH value, the number of negative charges on the surface of the hydrogel will be greater than the positive charge. Conversely, after swelling in a buffer solution with a low pH value, the number of negative charges on the surface of the hydrogel will be less than the positive charge. Methyl orange is negatively charged, and the loading rate of hydrogels soaked in a high pH value with more negative charges will be lower. The amino groups carried by chitosan itself can be protonated under acidic conditions, thereby strengthening the interaction between hydrogels, making the pores of the hydrogel smaller, and the number of solutes that can be accommodated decreases; under alkaline conditions, chitosan will be deprotonated, reducing the interaction of the hydrogel, the pores will become larger, and fewer water molecules can be hijacked by water tension, so the loading rate decreases. The dual effect of pH value makes the buffer solution with a neutral pH value have the highest loading rate for methyl orange.

[0076] 7. Methyl orange release detection

[0077] Methyl orange was used as a negatively charged model drug to evaluate the ability of chitosan / hyaluronic acid hydrogels treated with copper nitrate to release negatively charged drugs at different pH values. Chitosan / hyaluronic acid hydrogels treated with copper nitrate at different concentrations loaded with methyl orange were placed in buffers with different pH values ​​(4.92, 6.81, and 8.67) and released at 37°C and 150 rpm. The absorbance was measured at different time points. The release amount (V e :0.2mL,V0:10mL,C n : The concentration of the drug model in the solution after n samplings):

[0078]

[0079] The results are as follows Figure 7As shown, since the amount of methyl orange loaded in the hydrogel is approximately the same, the amount of hydrogel released is similar due to passive diffusion. Since methyl orange is negatively charged, the hydrogel loaded with methyl orange is repelled under high pH conditions, and its release rate is significantly lower than that under acidic and neutral conditions. Under acidic conditions, methyl orange should be released faster when it is positively adsorbed, but the actual situation is that the release rate under acidic conditions is slower than that under neutral conditions. This may be because chitosan is protonated under acidic conditions, so that the hydrogel network structure is denser and more stable, which makes the release of methyl orange slower, the porosity increase is smaller than that under neutral conditions, and the binding ability to methyl orange is stronger, which is stronger than the repulsive force generated by the protonation of chitosan, so the release rate is lower than the rate of methyl orange release from the hydrogel under neutral conditions.

[0080] 8. Conductivity detection

[0081] The hydrogel was cut into 1 cm*2 cm rectangles and its thickness was measured using a screw micrometer. 6 Hz for EIS measurement, and then the conductivity of the hydrogel was calculated by the formula (L: hydrogel length; R: hydrogel resistance; A: hydrogel cross-sectional area):

[0082] Conductivity (σ) = L / R*A

[0083] The results are as follows Figure 8 As shown in the figure, the conductivity of the hydrogel treated with copper nitrate is slightly lower than that of the hydrogel treated with copper sulfate. From the comprehensive analysis of mechanical properties and swelling properties, it can be inferred that the network structure of the chitosan hydrogel treated with copper sulfate is dense, and the network density of the hydrogel treated with copper nitrate is lower than that of copper sulfate. However, the swelling property of the copper nitrate hydrogel is higher than that of the copper sulfate hydrogel, and it can transfer protons faster, so the conductivity is slightly lower than that of the hydrogel treated with copper sulfate.

[0084] 9. Testing of photothermal performance

[0085] Cu 2+ It is a divalent metal ion. Due to the local surface plasma resonance phenomenon, it has a significant photothermal conversion effect, that is, within a specific wavelength range, Cu 2+ The energy of light can be converted into thermal effect, thereby changing the internal structure and performance of the hydrogel. The hydrogel samples of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were cut into squares with a length and width of 1.5 cm, and the hydrogels were irradiated with near-infrared light at a wavelength of 808 nm. The temperature of the hydrogel surface was recorded at regular intervals using a temperature detector. The results are as follows: Fig. 9As shown, the hydrogel that has not been treated with copper solution has no photothermal effect and cannot convert the light effect into thermal effect. When the hydrogel is treated with light-irradiated copper solution, it has obvious photothermal response ability. At room temperature, the hydrogel can be raised to a higher temperature, thereby changing the performance of the hydrogel through light. It can be seen that when copper nitrate solution is used to soak the hydrogel film, the hydrogel can have good mechanical properties and swelling properties, and also has excellent photothermal properties.

[0086] 10. Antibacterial properties

[0087] First, 40 mg of the hydrogel samples of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were immersed in 10 mL of a 15% (w / v) sodium lauroyl creatine solution. Load for 12 hours at a temperature of 37°C and a rotation speed of 150 rpm. Then release in deionized water for 6 hours under the same conditions. Collect the supernatant after centrifugation for later use. The Escherichia coli and Staphylococcus aureus cultured to the logarithmic growth phase were spread on LB medium, an Oxford cup was placed on the medium, 20 μL of supernatant was added to the Oxford cup, and cultured at 37°C for 12 hours. The size of the inhibition zone was recorded with a digital image, and its area was calculated. The results are as follows: Fig.10 As shown, copper nitrate-treated hydrogels are able to load and release sodium lauroyl sarcosinate, and have a significant inhibitory effect on common wound infection bacteria - Escherichia coli and Staphylococcus aureus, which lays the foundation for the application of hydrogels in the field of wound dressings.

[0088] The detailed description of a chitosan / hyaluronic acid hydrogel based on nitrate ion regulation and its preparation method and application with reference to the above-mentioned examples is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing chitosan / hyaluronic acid hydrogel based on nitrate ion regulation, characterized in that: The preparation method comprises the following steps: (1) heating and stirring sodium hyaluronate in water until it is completely dissolved, and then adding chitosan and stirring to make it evenly dispersed; (2) slowly adding glacial acetic acid solution to step (1) to completely dissolve the chitosan, and continuing to stir the reaction for 20 to 50 minutes; (3) allowing the reaction solution obtained in step (2) to stand and dry to form a hydrogel film; (4) The dried hydrogel membrane is immersed in a solution containing nitrate ions, and then repeatedly washed with deionized water until the pH of the water is neutral and then dried.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of sodium hyaluronate to chitosan is 0.08-0.1:0.25-0.

30.

3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of sodium hyaluronate in water is 0.05-0.07 g / mL.

4. The preparation method according to claim 1, characterized in that: In step (1), the temperature of the heating and stirring is 40 to 60°C.

5. The preparation method according to claim 1, characterized in that: In step (2), the pH of the glacial acetic acid solution is 2-4.

6. The preparation method according to claim 1, characterized in that: In step (3) and step (4), the drying temperature is 40 to 60°C.

7. The preparation method according to claim 1, characterized in that: In step (4), the solution containing nitrate ions is a copper nitrate solution.

8. The preparation method according to claim 1, characterized in that: In step (4), the concentration of the solution containing nitrate ions is 0.25-0.3 mol / L.

9. The chitosan / hyaluronic acid hydrogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the chitosan / hyaluronic acid hydrogel as claimed in claim 9 in drug loading or dressing.